Technology of an Aprioristic Objective Assessment of Distance Course Themes Complexity Based on Saati's Algorithm - A. A. Rybanov (Journal of Engineering Science and Technology Review, 2016)
In this article problems of determination the distance course theme’s complexity. The structure of a distance course represents an ontotlogiya in which each element has the value of weight coefficient, communications between model elements also have weight coefficients. For an assessment of complexity presented in distance course "Machine-dependent languages" themes it was aware to use the Saati’s method of the hierarchies analysis, procedure of check of expert estimates of complexity by that was also carried out. Also the assessment of quality of the ontologic model of a distance course which is given in the results description of the carried-out work was also executed.